2020
DOI: 10.9734/ijpss/2020/v32i1030331
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Mapping of Available Micro Nutrient Status in Relation to Soil Properties of Tomato Grown Soils of Chikkaballapura District, Karnataka

Abstract: GPS based soil survey was conducted in the tomato growing areas of Chikkaballapura district, Karnataka to map the soil fertility status by using Arc GIS 10.4 software. Seventy five surface soil samples were taken from the tomato growing areas of the district and analysed for texture, pH, EC, OC and micronutrients (Zn, CU, Fe, Mn, B) and zinc content in plant samples. The results revealed that the soils under investigation were acidic to alkaline in reaction, non saline, medium to high in organic matter content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
5
3
0
Order By: Relevance
“…For macronutrients these results are in conformity with the findings of Verma et al [29] for soils of Punjab. For micronutrients the results are in conformity with the findings of Kumar et al [30] and Prasad et al [17] at Jhabua district of Madhya Pradesh and Chikkaballapura district of Karnataka. Verma et al [29] reported that there is low nutrient index for N and Zn, high nutrient index for P, Cu, Fe and Mn and medium availability for K in major sugar cane growing soils of Punjab.…”
Section: Nutrient Index Of the Studied Soilssupporting
confidence: 91%
See 3 more Smart Citations
“…For macronutrients these results are in conformity with the findings of Verma et al [29] for soils of Punjab. For micronutrients the results are in conformity with the findings of Kumar et al [30] and Prasad et al [17] at Jhabua district of Madhya Pradesh and Chikkaballapura district of Karnataka. Verma et al [29] reported that there is low nutrient index for N and Zn, high nutrient index for P, Cu, Fe and Mn and medium availability for K in major sugar cane growing soils of Punjab.…”
Section: Nutrient Index Of the Studied Soilssupporting
confidence: 91%
“…The results are in conformity with the finding of Shukla [23] in soils of Pamgarh block in Janjgir-Champa district (C.G.). Similar findings were also reported by Prasad et al [17] in tomato growing soils of Chikkaballapura district of Karnataka.…”
Section: Availability Of Micro Nutrientssupporting
confidence: 90%
See 2 more Smart Citations
“…To overcome these problems foliar spray and soil application are being recommended but it is not a crop specific or soil specific recommendation. The tomato -growing soils in Karnataka are very much deficient in zinc [2,3]. Keeping the above facts in view the present study was under taken.…”
Section: Introductionmentioning
confidence: 94%